Effectiveness of phone reminders to improve adherence to anti-retroviral therapy : a meta-analysis - Abdullah Aliff Abdul Wahab,; Rosnah Ismail,; Halim Ismail,; Nazarudin Safian, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Adherence to anti-retroviral therapy (ART) regimens remains a difficult issue. Thus, it was hoped that the use of phone reminders would improve adherence. The Cochrane database was searched using selected keywords for this meta-analysis. We included randomised, controlled trials (RCTs) that utilised interventions with phone reminder and reported adherence outcomes, as the proportion of prescribed pills taken, the scores on an adherence questionnaire, or the follow-up rate. Two independent authors screened titles of article for inclusion, extracted the relevant data, and assessed articles for risk of bias. Seven RCTs published between 2010 and 2017 were selected for inclusion in this review. The sample size ranged from 76 to 631 participants. Most RCTs used short message service (SMS) and phone call reminders as interventions. The rate of adherence was 1.17-fold greater among those who received phone reminders than those who did not, which was statistically significant (Z = 2.86, p = 0.004). Those who received phone reminders showed a 17% higher likelihood for adherence compared with those who did not receive any phone reminder interventions. Phone reminders remain significantly effective means for improving adherence.